Symptoms of Diabetes - Linda B. Bobroff (EDIS)
Type 2 diabetes is a growing health concern for children as well as adults in the United States. Diabetes that is uncontrolled can lead to blindness, kidney disease, heart disease, and amputations. Early treatment to control blood glucose levels helps decrease a person’s chances of developing these health problems. Everyone should be tested for diabetes at their regular checkups. If you have any of the following symptoms of diabetes, see your health care provider right away! (Remember, sometimes type 2 diabetes has no symptoms.) This document is FCS8751, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 2005.